Could a hybrid cycling-running shoe offer time savings to triathletes?. (4th May 2022) - Sterns, Kyle; Hurt, James W.; Wilkinson, Ross D.; Kram, Rodger
Abstract: Triathletes almost universally use two shoe types; one for cycling and one for running. Though equally as efficient as cycling shoes during steady-state cycling, traditional running shoes impair cycling sprint performance. Newly developed running shoes, containing stiff carbon-fibre plates, may allow triathletes to use one pair of shoes for both cycling and running without sacrificing performance. Here, we describe a hybrid running-cycling shoe system, consisting of carbon-plated running shoes with magnetic pedal attachments and test whether it facilitates similar crank power and sprint cycling performance compared to a traditional road cycling shoe-pedal combination. The purpose of the present study was to quantify the possible disadvantage of cycling in running shoes during accelerations, even though accelerations comprise only a small portion of a triathlon cycling leg. Participants completed four standing, all-out, 50 m sprints in both shoe-pedal conditions on an uphill road (4.9% slope). On average, maximum 1 s mechanical power and 50 m mean power decreased by 8.5% ( p < .001) and 7.5% ( p < .001), respectively, when using the hybrid shoe-pedal combination. The decrease in power translated to only a 2.8% decrease in 50 m mean velocity ( p < .001). Some participants expressed apprehension about the novel magnetic shoe-pedal interface which may explain a portion of the decrease in performance. Overall, we find that for triathletes, using hybrid running-cycling shoes would incur little performance disadvantage during accelerations on the bike. Not having to change shoes would allow for a faster bike-to-run transition.